The impact of the traffic infrastructure on the tourist destination - Ace Milenkovski; Mijalce Gjorgievski; Dejan Nakovski (UTMS Journal of Economics, 2020)
Tourism activity in the region depends on internal and external factors that affect the level of tourist development of the destination. Internal and external tourism factors complement each other and thay are interdependent. These factors are not constant, but it may come to their change over time, especially when it comes to anthropogenic factors. The changes can directly affect negative or positive on development of the tourist destination. The authors of this paper aim to present how the changed anthropogenic external factors shown through the traffic infrastructure, and how they affect the transformation of the level of tourist development of the region, through the example of the new traffic infrastructure in the Republic of North Macedonia. The changes caused by the newly created external factors, in the future will initiate adjustment and correction of the existing plans for tourist development of the destination and a new managerial approach in tourism planning.
Keywords: L83; Z32; I15; O18; 330; tourism policy; development; tourist demand; tourism factors